Authority of Traditional Leadership in Natural Resource Management in the Meyah Tribe of Manokwari - Mandacan, Noris; Hammar, Roberth K.R.; Labobar, Filex M. (IHSA Institute, 2025)
This study examines the leadership structure and authority of the Meyah customary law community in managing natural resources in Manokwari Regency, West Papua. Using a qualitative approach using legal ethnography methods combined with an empirical juridical model, this study highlights how living customary law serves as the primary foundation for maintaining the ecological, spiritual, and social balance of the community. The findings indicate that tribal chiefs and customary councils play a central role in establishing customary rules related to the management of customary lands, customary forests, rivers, and sacred areas, based on the values ??of deliberation and respect for ancestors. However, this authority faces serious challenges, such as the dominance of state law based on formal documents, overlapping customary territories with investment permits, and weak recognition of customary institutions in public policy. This article concludes that strengthening customary authority requires structural and legal strategies, such as the issuance of Perdasus, participatory mapping of customary territories, community legal literacy, and strengthening the political representation of indigenous communities. It is crucial as part of protecting constitutional rights and preserving local wisdom-based natural resource governance